Avaliação da Aprendizagem em Processo: limites e possibilidades de uso em uma Escola da Rede Estadual de São Paulo - Sousa, Maria Eliane Maia (2015)
This work aimed to investigate the Learning Evaluation as a Process (LEP) use by teachers and coordinator teachers in a school of the state education network from the city of São Paulo, through a case study. Data were collected using observation sessions, semi-structured interviews, and a discussion group. The interviews were carried out with a school board supervisor, the director, one cycle II coordinator, two teachers from Portuguese and Mathematics disciplines, and one teacher that do not directly participate of the LEP. For the discussion group, eleven students from the final years of the elementary school were selected. This research used the studies of Bonamino and Sousa (2012) about the evaluation of Brazilian basic education, Gimenes et al (2013), Alavarse et al (2013), and Morasco Junior and Gama (32013) that investigated the use of external evaluations, as theoretical background. In order to understand the concepts of learning evaluation and formative assessment, this study relied on the works of Fernandes (2009), Hadji (2001), and Luckesi (2011). The analysis of the data and their allocated categories shown that was possible to identify different possibilities for the use of the LEP by teachers and the management team, as well as its potential use in the planning of students learning improvement actions